Assessment of Cost and Embodied Carbon for Masonry Structures Located in Low and High Seismic Zones. (2017) - Cobîrzan, Nicoleta; Voinea, Mirela; Kopenetz, Ludovic; Munteanu, Constantin; Balog, Anca-Andreea; Tămaş, Florin
Abstract: Based on the sustainable criteria, the paper presents the analysis of cost, in euro/material, and environmental impact expressed by the embodied carbon in materials and heat gains through the glazing areas of two residential dwellings. The buildings have the same architectural design but different types of masonry, one is made of unreinforced masonry and is located in Cluj-Napoca (low seismic zone) and the second one is a confined masonry, located in Bucharest (high seismic zone). The results show that the quantity of materials, the embodied carbon in materials and the construction costs of buildings vary with up to 20% and emphasize the importance of their analysis in the building's design stage.